Analysis of a nuclear localization signal of simian virus 40 major capsid protein Vp1. - Ishii, N (1996)
The nuclear localization signal of the major structural protein, Vp1, of simian virus 40 was further defined by mutagenesis. The targeting activity was examined in cells microinjected with SV-Vp1 variant viral DNAs bearing either an initiation codon mutation of the agnoprotein or mutations in the Vp1 coding sequence or microinjected with pSG5-Vp1 and pSG5-Vp1 mutant DNAs in which Vp1 or mutant Vp1 is expressed from simian virus 40 early promoter. The Vp1 nuclear localization signal functioned autonomously without agno-protein once the Vp1 protein was synthesized in the cytoplasm. The targeting activity was localized to the amino-terminal 19 residues. While replacement of cysteine 10 with glycine, alanine, or serine did not affect the activity, replacement of arginine 6 with glycine caused the cytoplasmic phenotype. When multiple mutations were introduced among residue 5, 6, 7, 16, 17, or 19, the targeting activity was found to reside in two clusters of basic residues, a cluster of lysine 5, arginine 6, and lysine 7 and a cluster of lysine 16, lysine 17, and lysine 19. The clusters are independently important for nuclear localization activity.